Optimization Of Product Diversification and Product Quality Through Digital Sewing Machine Technology and Copper Wax Melting Vats for Batik Craftsmen in Tanjung Bumi - Liosten Rianna Roosida Ully; Muhammad Syahrul Borman; Safrin Zuraidah; Ichlas Wahid (Pascasarjana Universitas Mataram, 2025)
Community Empowerment for Regional Superior Products (PM-UPUD), with the title